2011
DOI: 10.4049/jimmunol.1002980
|View full text |Cite
|
Sign up to set email alerts
|

Primary Human CD4+ T Cells Have Diverse Levels of Membrane Lipid Order That Correlate with Their Function

Abstract: Membrane lipid microdomains (lipid rafts) play an important role in T cell function by forming areas of high lipid order that facilitate activation. However, their role in regulating T cell differentiation and function remains controversial. In this study, by applying a new approach involving microscopy and flow cytometry, we characterize membrane lipid order in ex vivo primary human CD4+ T cells. We reveal that differential membrane lipid order dictates the response to TCR stimulation. T cells with high membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 53 publications
1
63
0
Order By: Relevance
“…Our recent findings show that changes in the composition and organization of lipids in the plasma membrane can influence T cell function (16). In order to characterize total T cell GSL composition, lip-…”
Section: Dysregulated Gsl Expression In Cd4 + T Cells From Patients Wmentioning
confidence: 99%
“…Our recent findings show that changes in the composition and organization of lipids in the plasma membrane can influence T cell function (16). In order to characterize total T cell GSL composition, lip-…”
Section: Dysregulated Gsl Expression In Cd4 + T Cells From Patients Wmentioning
confidence: 99%
“…Depending on the device available, previous studies have used different band passes centered around 550 and 660 nm to quantify the blue shift of the dye on living material. For example, the horizontal, light gray bands correspond to 500 to 580 nm and 620 to 750 nm (Miguel et al, 2011), while the horizontal, dark gray bands correspond to 505 to 550 nm and a long pass higher than 650 nm (Liu et al, 2009). The colored, vertical band pass bars correspond to the values used in our experimental setup to calculate an accurate red/green ratio (545-565 nm in red and 635-655 nm in green).…”
Section: Characterization Of Pm Order Level In Living Tobacco Cellsmentioning
confidence: 99%
“…4), which affirms the robustness of this parameter in evaluating the order level of the analyzed zone. The degree of cell membrane order evaluated from the emission properties of the dye can also be expressed as a generalized polarization parameter (GP), defined as (I550 -I660)/(I550 + I660), which increases with ordered level (Owen et al, 2010b(Owen et al, , 2012aMiguel et al, 2011). Interestingly, the fact that tobacco cell PM can be observed as a continuous distribution centered on a unique peak by using either the GP (Supplemental Fig.…”
Section: Cryptogein Induces a Spatial Rearrangement Of The Pm Order Lmentioning
confidence: 99%
“…Several prior studies have shown how lipid accumulation in lymphocytes impacts their differentiation and activation323350515253. Accumulation of intracellular cholesterol stimulates CD4 + 3233 and γδ53 T cell proliferation and activation.…”
Section: Discussionmentioning
confidence: 99%